Recovery of B-cell homeostasis after rituximab in chronic graft-versus-host disease - Sarantopoulos, Stefanie (American Society of Hematology, 2011)
Investigation of the effects of rituximab (anti-CD20) on B-cell-activating factor of the tumor necrosis factor family (BAFF) and B cells would better define the significance of B-cell homeostasis in chronic graft-versus-host disease (cGVHD) pathophysiology. We studied 20 cGVHD patients at a median of 25 months after rituximab treatment when most patients had recovered total B-cell numbers. A total of 55% of patients had stable/improved cGVHD, and total B-cell numbers in these patients were significantly higher compared with rituximab-unresponsive patients. Although total B-cell number did not differ significantly between cGVHD groups before rituximab, there was a proportional increase in B-cell precursors in patients who later had stable/improved cGVHD. After rituximab, BAFF levels increased in all patients. Coincident with B-cell recovery in the stable/improved group, BAFF/B-cell ratios and CD27(+) B-cell frequencies decreased significantly. The peripheral B-cell pool in stable/improved cGVHD patients was largely composed of naive IgD(+) B cells. By contrast, rituximab-unresponsive cGVHD patients had persistent elevation of BAFF and a predominance of circulating B cells possessing an activated BAFF-R(Lo)CD20(Lo) cell surface phenotype. Thus, naive B-cell reconstitution and decreased BAFF/B-cell ratios were associated with clinical response after rituximab in cGVHD. Our findings begin to delineate B-cell homeostatic mechanisms important for human immune tolerance.